The Role of Religious Education in Dealing with the Issue of Radicalization among Students - Agus Subairi (PT. Anagata Sembagi Education, 2024)
Radicalization has become a serious threat in the world of education, especially among students who are in the developing stage of self-identity search, where curiosity and emotional instability make them vulnerable to the influence of radical ideology. Religious education, in this context, plays a central role in shaping students' character by instilling values of moderation, tolerance, and respect for diversity. This study aims to explore the role of religious education in preventing radicalization, using a descriptive qualitative method with data collection techniques through in-depth observation and interviews involving teachers, students, principals, and parents. The focus of the research is on the implementation of religious moderation values in schools as an effort to build students' critical attitudes towards extremist ideologies. The results of the study show that inclusive, interactive, and collaborative teaching approaches in religious education, both in the classroom and by involving the external community, play an important role in fostering tolerant characters and being able to reject radical narratives. The study highlights the importance of collaboration between schools and families, as well as the need for digital literacy education to strengthen students' resilience to exposure to extremist content on social media. The implications of this study include the need to integrate materials relevant to actual issues in the religious education curriculum, as well as the development of community-based educational programs that involve families and communities as additional bulwarks of protection for students.